Social Networks and Sociology Graduates’ Employment - Thi Thu Thanh, Nguyen (VNU Journal of Science: Education Research; Vol 34 No 1, 2018)
Social networks influence various aspects of both material life and spiritual life. The social relationships are clearly demonstrated in the labour market. Many domestic and international researches show that social network is an effective unofficial channel for job search. The study of the 2015 and 2016 Sociology graduates from Vietnam National University, Hanoi (VNU) University of Social Sciences and Humanities provides a profound understanding of the role of social networks in the graduates’ job search and their professional development.